Transposable elements: Uniqueness and applications - Cahyo Budiman; Rafida Razali; Abdul Ashraf Rasid; Kathrie Rubil; Mardani Abdul Halim (Malaysian Society for Microbiology, 2023)
The study of transposable genetic elements, a cornerstone of molecular genetics, offers profound insights into the dynamic nature of genetic material. This exploration encompasses various types found in bacteria, including insertion sequences, composite and non-composite transposons. These elements are instrumental in shaping bacterial genomes by facilitating the movement of genetic information, driving evolution and contributing to genetic diversity. Understanding the mechanisms of transposition is essential for unravelling the intricate processes governing genetic rearrangements. Replicative and conservative transposition mechanisms, exemplified by the Tn3 family and phage Mu, illustrate the remarkable adaptability of these systems in reshaping genomes. However, it is the transposon Tn5 that steals the spotlight as a versatile molecular genetics tool. Tn5's transposition mechanism, characterized by precise control over gene expression, translational regulation, protein localization and the induction of conditional mutations, empowers researchers to dissect gene regulation intricacies with unprecedented accuracy. Transposable genetic elements, epitomized by Tn5, are indispensable instruments in molecular genetics. They allow researchers to navigate the intricate landscape of genetics, exploring gene regulation, protein function, and genetic diversity with unparalleled precision. These elements continue to be at the forefront of molecular genetics research, driving innovations that deepen our understanding of the fundamental mechanisms governing life's genetic code.